Aboriginal Peoples Survey, 2006 [Canada]: Adults ... : Adults ... - Statistics Canada. Social And Aboriginal Statistics Division. (Borealis, 2023)
The 2006 Aboriginal Peoples Survey (APS) provides data on the social and economic conditions of First Nations people living off reserve, Métis and Inuit. Its specific purpose was to identify the needs of Aboriginal people focusing on issues such as health, language, employment, income, schooling, housing, and mobility. The survey was designed and implemented in partnership with national Aboriginal organizations. This product contains information for the Aboriginal adult population (15 years and over). ... : Notes: Interviews for the APS were conducted in the fall of 2006 through the spring of 2007.; ...